Seven Ozobot messengers: a story by Buzzati between mathematics and robotics - Matteo Torre (Firenze University Press, 2019)
This paper describes the didactical, methodological and content choices referred to an educational pathway inspired by a story by Dino Buzzati, titled "The seven messengers". The aim is to deepen and introduce basic mathematical and physical concepts. The idea is not new in the educational research. Nonetheless, the innovative aspect of the proposal is the use of educational robotics to facilitate learning abstract scientific concepts. The experimentation concerns 35 students of the first year of the scientific high school, attending a transversal class of the L. B. Alberti Institute in Valenza (AL) that joined the Liceo Matematico project promoted by the Department of Mathematics G. Peano of the University of Turin.   I sette messaggeri Ozobot: un racconto di Buzzati tra matematica e robotica Questo articolo descrive le scelte didattiche, metodologiche e contenutistiche di un percorso didattico che prende spunto da un racconto di Dino Buzzati, "I sette messaggeri", per approfondire e introdurre concetti matematici e fisici di base. L'idea non è nuova nel panorama della ricerca in didattica, ma l'aspetto innovativo introdotto in questa proposta sta nell'uso della robotica educativa per facilitare l'apprendimento di concetti scientifici astratti. La sperimentazione didattica riguarda una classe trasversale dell'Istituto L. B. Alberti di Valenza (AL) composta da 35 alunni, tutti del primo anno del liceo scientifico, che hanno aderito al progetto Liceo Matematico promosso dal Dipartimento di Matematica G. Peano dell'Università di Torino.